Assistance With Optimization Of Digital Marketing And Financial Management In The Ana Macrame Crafts Business Group, West Sumbawa - Wati, Lidia; Hari Asgar; Amrussalam (Universitas Nahdlatul Ulama Surabaya, 2024)
Micro, Small and Medium Enterprises (MSMEs) are a type of small business that play a significant role in improving and growing the community's economy. One of the MSMEs in West Sumbawa Regency that is a partner in this PKM program is the Ana Macrame Craft Business Group. Current marketing at Mitra still mostly uses traditional marketing methods due to a lack of ICT mastery, which causes a lack of competitiveness compared to other modern and online-based craft businesses, especially competitiveness to attract the attention of young people who are considered consumptive and rely more on online shopping. In the field of financial management, partners have not recorded business financial transactions and have not prepared financial books. This can cause the partner not to know exactly how much the business is developing and how much the value of the partner's business assets is compared to the revenue generated or cash availability. The worst risk from this condition is that the Partner's business could go bankrupt in the future This activity aims to improve the partners' skills in digital marketing and business financial management. It is hoped that through optimizing digital marketing, Partners can expand their marketing reach to various regions in Indonesia. Meanwhile, through good business financial management, it is hoped that partners can control business continuity and develop the business in the future. The results and outcomes of this activity are for digital marketing management, partners have a website landing page and domain hosting while in financial management partners input financial reports on the